Improving Students’ Speaking Performance through the KISS Method in EFL Classrooms - Agung Purnama; Dzulfikri Dzulfikri (MASI Mandiri Edukasi, 2026)
This study employs Classroom Action Research (CAR) to investigate the effectiveness of the KISS (Keep It Short and Simple) method in enhancing students’ speaking performance in English as a Foreign Language (EFL) classrooms. The research was conducted at MA Al-Azhar Grobogan, involving a class of Grade XI students in a formal EFL setting. The participants consisted of approximately 25 students. The study was carried out through two intervention cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through speaking tests, classroom observations, interviews, and questionnaires. The findings indicate a significant improvement in students’ speaking performance across the cycles, particularly in terms of fluency, clarity, and confidence. The implementation of the KISS method helped reduce students’ speaking anxiety, improve idea organization, and increase their motivation to participate actively in classroom activities. Furthermore, students demonstrated greater engagement and confidence in expressing their ideas throughout the learning process. In conclusion, the KISS method proves to be an effective instructional strategy for improving students’ speaking skills within this classroom context. However, the findings are limited to the specific participants and setting of this study. Therefore, further research is recommended to examine the applicability of the KISS method in broader educational contexts and with larger participant groups.